The road to the NFL - Green, Tim, 1963- (New York : Scholastic, Inc., 2003)
"Drawing on interviews with six of today's biggest players, this is the real story of how some of the toughest, most talented guys came to play the game."--Cover back.
Michael Vick -- Brain Urlacher -- David Dixon -- Jeff Garcia -- John Lynch -- Anthony Thomas.
Keywords: National Football League; Football players -- Biography